UNSUSTAINABILITY OF GEOGRAPHIC SPACE IN QUEBRANGULO - AL - Melo, Felippe Pessoa de (2013)
The municipality of Quebrangulo-AL and constantly plagued by floods, which pose a risk to the local population lives and cause great damage geoenvironmental. In order to understand this phenomenon, using the technologies of Remote Sensing and Geographic Information System (GIS), for making the thematic maps relating to: hipsometria, geology, drainage, municipal boundaries. In possession of this material could make a geoenvironmental analysis, the dynamics of use and occupation of land in the city, which provided theoretical and methodological implementation of public policies for sustainable government.